The look of eleuthería: an overview of conscious objection from ethics and human rights - Castañeda Camacho, Gustavo Eduardo (2024)
Conscientious objection is a complex and multifaceted issue that encompasses cultural, ethical, moral, legal and educational aspects. The text advocates recognizing conscientious objection as a fundamental human right, especially in contexts such as medical care, but also highlights the need to find a balance that guarantees other rights, such as the right to health. Education is presented as a crucial tool to facilitate the understanding and exercise of these rights, promoting tolerance and reflection on ethical and moral issues. In addition, emblematic cases and recent legislation in Mexico are mentioned as concrete examples of how this issue is addressed in practice. In summary, the text advocates a comprehensive and equitable approach when dealing with conscientious objection in different areas of society.